The mortal instruments [videorecording (DVD)] : city of bones - Clare, Cassandra ([publisher not identified], 2013)
Clary Fray, a seemingly ordinary teenager, discovers she is the descendant of a line of Shadowhunters, a secret cadre of young half-angel warriors locked in an ancient battle to protect our world from demons. After the disappearance of her mother, Clary joins forces with a group of Shadowhunters who introduce her to a dangerous alternate New York City called Downworld, filled with demons, warlocks, vampires, werewolves and other deadly creatures.